Análisis del manejo de ambientes de aprendizaje en las aulas de niños de 4 a 5 años en una institución particular y otra municipal - Amagua Mena, Gabriela Ximena (2015)
Undeniably, the relationship between the environment and learning. Understanding learning in its broadest and accurately as the relationship between the learner and the object that is learned, so it becomes important to recognize that all learning is generated in an atmosphere when it is pedagogically thought. Learning environments are places where children must build capacity to interact, explore and above all to share with other children of their environment. It is essential to take into account certain parameters that allow the child to feel safe, free and in confidence with the teacher and their peers, This research addresses important issues that are distributed in four chapters that talk about the management of learning environments, the importance of an adequate learning environment, socialization among children, resources, distribution of space, the methodology more successful for learning, classroom design and organization must have for stimulation and intellectual and social development of children. In the analysis of interviews with teachers Private institution Giordano Bruno and Municipal Employees CEMEI located in the urban sector of Quito they were applied. As an observation sheet held in different classrooms in children 4-5 years of both institutions. Getting information on the different learning environments that are working in different institutions and the type of socialization that is generated from this.